2016
DOI: 10.1177/0194599816648111
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes after Salvage Transoral Laser Microsurgery for Laryngeal Squamous Cell Carcinoma

Abstract: TLM is a successful surgical option for recurrent laryngeal cancer with acceptable functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…The series of Puxeddu et al [15] is a two-center retrospective case series, with results of one included center updated in a later publication by Piazza et al [16], which, in turn, was updated by Del Bon et al [17]. Most authors reported on series of rT1 to rT2 glottic cancer, while some authors also included more advanced glottic cases (rT3 or even rT4) [11••, 1821] or supraglottic recurrences [14, 18, 2022]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The series of Puxeddu et al [15] is a two-center retrospective case series, with results of one included center updated in a later publication by Piazza et al [16], which, in turn, was updated by Del Bon et al [17]. Most authors reported on series of rT1 to rT2 glottic cancer, while some authors also included more advanced glottic cases (rT3 or even rT4) [11••, 1821] or supraglottic recurrences [14, 18, 2022]. …”
Section: Resultsmentioning
confidence: 99%
“…Tracheotomy was not required as a routine procedure (in contrast to open partial laryngeal surgery) with most studies reporting a 0% tracheotomy rate. However, in four series [11••, 20, 21, 24], postoperative tracheotomy proved necessary in 2 to 22% of cases, with decannulation times ranging from 4 days to more than 4 months. The nasogastric tube feeding rate ranged from 0 to 23.5% with all nasogastric tubes being removed after 8 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations